Working and health conditions of drivers of a public transportation company in bogotá, d.c. (2001)
A cross-sectional descriptive study was carried out. Aimed at identifying the working conditions of the drivers of a public transportation company in Bogotá. A technical inspection was done in some of the routes covered by the company. 194 drivers were included; all of them were interviewed, and submitted to medical and physiotherapeutic exams, audiometry, examination of visual acuity and visual field, spirometry and biochemical tests (glycemia, lipid profile, glycosylated hemoglobin and carboxyhemoglobin blood levels before and after working exposition). The results showed that these workers are mainly exposed to the poor state of the streets, chemical pollutants, glaring, noisy environments, competition with other public transportation services ("cents war"), poor lighting in the streets and sudden temperature changes. Gastrointestinal alterations, anxiety, visual changes, depression, otorhinolaryngological manifestations, osteomuscular signs and symptoms (muscular retractions in the lower limb muscles and in the paravertebral muscles; alterations in the dorsal and lumbar spine) changes in the oral cavity, eyes and its annexes and nose, overweight, obesity, presbyopia, astigmatism, lipemia and abnormal carboxyhemoglobin levels were the most frequently reported changes after working exposition. One third of the drivers complained of high stress levels. The findings suggest discoveries suggest that the working conditions can cause adverse effects on health. It is recommended that future analytical studies be carried out in order to investigate the probable associations between the working risk factors and the adverse effects on health found here.